Gastroduodenal, intestinal and colonic permeability during anticancer therapy - Melichar, Bohuslav; Hyšpler, Radomír; Kalábová, Hana; Dvořák, Josef; Tichá, Alena; Zadák, Zdeněk (Hepato-gastroenterology, 2011)
BACKGROUND/AIMS: Measurement of the permeability of gut mucosa may offer a method for objective assessment of mucosal dysfunction during cancer therapy. METHODOLOGY: Gastroduodenal, intestinal and colonic permeability was studied by using capillary gas chromatography and measuring urinary sucralose, sucrose, lactulose, xylose and mannitol levels. A total of 41 patients with metastatic colorectal carcinoma or epithelial ovarian carcinoma were studied before and during chemotherapy with the combinations of cetuximab, irinotecan, 5-fluorouracil and leucovorin; bevacizumab, oxaliplatin, 5-fluorouracil and leucovorin; or paclitaxel/ platinum. RESULTS: Compared to pretreatment values, a significant increase was observed during the first cycle of therapy in the percentage of sucrose, sucrose/mannitol ratio, lactulose and lactulose/ mannitol ratio in patients treated with the combination of bevacizumab, oxaliplatin, 5-fluorouracil and leucovorin. No changes were observed in patients treated with cetuximab, irinotecan, 5-fluorouracil and leucovorin, but these patients had significantly higher baseline percentage of lactulose excretion and sucrose/mannitol and lactulose/ mannitol ratios. CONCLUSIONS: An increase in gastroduodenal and intestinal permeability was observed in patients treated with bevacizumab, oxaliplatin, 5-fluorouracil and leucovorin, but not in patients treated with cetuximab, irinotecan, 5-fluorouracil and leucovorin. No significant increase in colonic permeability was observed, but the present method was insufficient to detect colonic permeability in a significant proportion of patients.
Keywords: senioři; Aged; Middle Aged; protinádorové látky; Permeability; Intestinal Mucosa; střevní sliznice; Antineoplastic Agents; žaludeční sliznice; Duodenum; Gastric Mucosa; sacharosa; duodenum; Adult; Sucrose; Colon; permeabilita; dospělí; lidé středního věku; lidé; Humans; kolon